PENDIDIKAN ANAK DALAM SERAT WULANG SUNU KARYA SUNAN PAKUBUWONO IV: Sebuah Analisis Isi - Iflahathul Chasanah; Abdul Munip; Mukhibat Mukhibat (IAIN Ponorogo, 2018)
The paper aims to describe the child education in Serat Wulang Sunu written by Sunan Pakubuwono IV. The writer focuses on content, purpose, subject matter, a method of education and also the relevance of educational values of Serat Wulang Sunu currently. The result is Serat Wulang Sunu teach the children behavioral ethics to parent and the other. The education purpose is creating the child dutiful to the parents as a child ideal profile. Subject matter thought by Serat Wulang Sunu involved politeness, respect to parents, command, and prohibition with parents. The method that used in Serat Wulang Sunu thought through the advice, prohibition, threat, and an appointment. The thought and education values in Serat Wulang Sunu still relevance when used in the education system today. Serat Wulang Sunu has universal thought and values that must be preserved for human life.هذه الكتابة لتصريح تربية الطّللّاب في